Preparation of Fe3O4/TiO2/ZnO Composite as a Photocatalyst for the Degradation of Methylene Blue: Optimization and Light Source Variations - Duwi Devi Wulandari; Noor Hindryawati; RR Dirgarini Julia Nurlianti Subagyono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
The Fe3O4/TiO2/ZnO (MTZ) composite was synthesized by preparing Fe3O4 via the coprecipitation method, TiO2 via the hydrothermal method, and ZnO via the precipitation method. The three oxides (Fe3O4, TiO2, and ZnO) were composited using the solid-state method with varying mass ratios (1:2:1, 2:1:1, 1:1:2, and 1:1:1) and calcined at 600°C for 4 h to obtain MTZ composites. The composites were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and particle size analysis (PSA). The results indicated that the Fe3O4/TiO2/ZnO composite with a 1:1:2 ratio (MTZ3) exhibited the most favorable properties. MTZ3 was evaluated as a photocatalyst for methylene blue degradation under UV light, with variations in irradiation time, catalyst mass, and dye concentration. Further tests were conducted under sunlight and dark conditions using both the composite and its individual oxides (Fe3O4, TiO2, and ZnO). Reuse tests assessed the stability of MTZ3 after repeated cycles. Under optimum conditions (catalyst mass 0.4 g, methylene blue concentration 20 ppm, irradiation time 60 min), MTZ3 achieved 80.4% degradation under UV light. Under sunlight, degradation efficiency reached 98.7%, while under dark conditions it was only 4.5%. Reuse tests demonstrated consistent performance over three cycles, maintaining 80.4% degradation, surpassing previous studies on Fe3O4–TiO2 (1:2) composites, which achieved 67.49% degradation over two cycles. These results suggest that the MTZ3 composite is a stable and efficient photocatalyst with excellent potential for dye degradation under various light sources.